Microbiome, bile acids, and obesity: How microbially modified metabolites shape anti‐tumor immunity. Issue 1 (22nd April 2020) - Sipe, Laura M.; Chaib, Mehdi; Pingili, Ajeeth K.; Pierre, Joseph F.; Makowski, Liza
Abstract: Bile acids (BAs) are known facilitators of nutrient absorption but recent paradigm shifts now recognize BAs as signaling molecules regulating both innate and adaptive immunity. Bile acids are synthesized from cholesterol in the liver with subsequent microbial modification and fermentation adding complexity to pool composition. Bile acids act on several receptors such as Farnesoid X Receptor and the G protein‐coupled BA receptor 1 (TGR5). Interestingly, BA receptors (BARs) are expressed on immune cells and activation either by BAs or BAR agonists modulates innate and adaptive immune cell populations skewing their polarization toward a more tolerogenic anti‐inflammatory phenotype. Intriguingly, recent evidence also suggests that BAs promote anti‐tumor immune response through activation and recruitment of tumoricidal immune cells such as natural killer T cells. These exciting findings have redefined BA signaling in health and disease wherein they may suppress inflammation on the one hand, yet promote anti‐tumor immunity on the other hand. In this review, we provide our readers with the most recent understanding of the interaction of BAs with the host microbiome, their effect on innate and adaptive immunity in health and disease with a special focus on obesity, bariatric surgery‐induced weight loss, and immune checkpoint blockade in cancer.